The Role of Music in an Arts-Based Qualitative Inquiry - Norma Daykin (International Journal of Qualitative Methods, 2004)
In this article, the author discusses the expressive potential of music and how it can be applied in an arts-based qualitative research project. The limitation of music, and other forms of non-verbal forms of artistic expression, are discussed. The conclusion is that music can serve well as a supplementary form of expression in arts-based research, but, like many texts, even those whose meaningfulness is taken for granted, cannot stand alone.